2019
DOI: 10.3390/app9122512
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in Liquid-Crystal-Aided Nanotechnology and Nanoscience

Abstract: The research field of liquid crystals and their applications is recently changing from being largely focused on display applications and optical shutter elements in various fields, to quite novel and diverse applications in the area of nanotechnology and nanoscience. Functional nanoparticles have recently been used to a significant extent to modify the physical properties of liquid crystals by the addition of ferroelectric and magnetic particles of different shapes, such as arbitrary and spherical, rods, wires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 445 publications
(519 reference statements)
2
60
0
9
Order By: Relevance
“…Such a behavior promises a simple and viable method for manipulating soliton motion, in fact along any trajectory and to any destination desired. Furthermore, it has been reported that distorted LC regions can attract colloidal particles 9,37 . Since these solitons are actually self-confined director deformations, they can even be used to transport micro-cargos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a behavior promises a simple and viable method for manipulating soliton motion, in fact along any trajectory and to any destination desired. Furthermore, it has been reported that distorted LC regions can attract colloidal particles 9,37 . Since these solitons are actually self-confined director deformations, they can even be used to transport micro-cargos.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid crystals (LCs) provide especially rich opportunities for the studies of solitons [6][7][8] . LCs that combine properties of isotropic liquids and crystalline solids are extremely sensitive to a variety of external stimuli, such as electric and magnetic fields, and exhibit fascinating optical behavior 9 . Studies on solitons in LCs have been carried out for over 5 decades 10 .…”
mentioning
confidence: 99%
“…Due to their low abundance in the systems, solvent molecules end up being confined in regions with the same polarity, while the amphiphiles form strong templating cages. New regions, characterized by the presence of liquid crystal phases, are generally formed [37,38]. It is obvious that the specific mixture of various amphiphiles can trigger the arising of emerging properties that are suitable for the construction of novel advanced devices in many diverse nanotechnology areas, such as displays, nanosensors and biotechnology applications [37,38].…”
Section: Liquid Crystalline Nanostructuresmentioning
confidence: 99%
“…Extensive achievements have been made in display materials since the 1970s involving the famous material such as liquid crystal (LC), leading to manufacturing of outstanding organic light emitting displays (OLEDs). With the rapid development and achievements over the last decade, many researchers moved their exploration to the new era of LCs applications such as biosensors [1], robotics, telecommunications and nano-manipulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid of LCs-nanomaterials can modify the original chemical and physical properties of LCs. It can also modify the nanomaterial properties by manipulating and ordering LCs that can obtaine additional benefits from LCs or nanomaterials themselves for their new state and properties [2].…”
Section: Introductionmentioning
confidence: 99%